Vapor-phase polymerized poly(3, 4-ethylenedioxythiophene) (PEDOT)/TiO2 composite fibers as electrode materials for supercapacitors. (10th January 2017) - Tong, Linyue; Liu, Jian; Boyer, Steven M.; Sonnenberg, Laura A.; Fox, Maggie T.; Ji, Dongsheng; Feng, Jun; Bernier, William E.; Jones, Wayne E.
Graphical abstract: Highlights: A vapor-phase polymerization method resulted in PEDOT/TiO2 composite fibers. Composite fiber electrodes result in high, reversible capacitance in supercapacitors. PEDOT polymerization temperature affected the capacitance of the resulting fibers. Rutile/anatase ratio of TiO2 fibers affected the capacitance of the resulting fibers. Abstract: Vapor-phase polymerized poly(3, 4-ethylenedioxythiophene) (PEDOT)/TiO2 composite fibers were fabricated and applied as the supercapacitor electrode materials. TiO2 fibers were prepared as substrates for the vapor-phase polymerization process, by electrospinning and calcination in air. The symmetric supercapacitor cells assembled with the resulting composites were studied by a series of electrical measurements including cyclic voltammetry, charge-discharge characterization and electrochemical impedance spectroscopy. To further understand the capacitive behavior, the band gap energy of the composite fibers and the specific surface area of TiO2 fibers calcined at varied temperatures were measured. The highest specific capacitance of PEDOT on TiO2 fibers to date, 87.9 F g −1, was achieved with the composite fibers prepared by vapor-phase polymerization at 50 °C on the TiO2 fibers calcined at 550 °C. The pseudocapacitance and the reversibility of PEDOT were improved in comparison to other PEDOT/TiO2 binary composites.